White matter lesions and temporal lobe atrophy related to incidence of both dementia and major depression in 70‐year‐olds followed over 10 years. (18th January 2015) - Gudmundsson, P.; Olesen, P. J.; Simoni, M.; Pantoni, L.; Östling, S.; Kern, S.; Guo, X.; Skoog, I.
<x xml:space="preserve">Abstract</x> Background and purpose A number of studies have suggested associations between dementia and depression in older adults. One reason could be that these disorders share structural correlates, such as white matter lesions (WMLs) and cortical atrophy. No study has examined whether these lesions precede both dementia and depression independently of each other in the general population. Methods Whether WMLs and cortical atrophy on computed tomography predict dementia and depression was investigated in a population‐based sample of 70‐year‐olds (n = 380) followed over 10 years. Exclusion criteria were dementia, major depression, history of stroke and a Mini‐Mental State Examination score below 26 at baseline in 2000–2001. Dementia was diagnosed according to the Diagnostic and Statistical Manual of Mental Disorders, third edition, revised, and depression according to the Diagnostic and Statistical Manual of Mental Disorders, fifth edition. Primary outcomes included dementia and major depression at 10‐year follow‐up. Results Adjusted logistic regression models, including both WMLs and temporal lobe atrophy, showed that moderate to severe WMLs [odds ratio (OR) 3.96, 95% confidence interval (CI) 1.23–12.76] and temporal lobe atrophy (OR 2.93, 95% CI 1.13–7.60) predicted dementia during a 10‐year follow‐up independently of major depression. Similarly, both moderate to severe WMLs (OR 3.84, 95% CI 1.25–11.76) and temporal lobe atrophy (OR 2.52, 95% CI 1.06–5.96) predicted depression even after controlling for incident dementia. Conclusion White matter lesions and temporal lobe atrophy preceded 10‐year incidence of both dementia and depression in 70‐year‐olds. Shared structural correlates could explain the reported associations between dementia and depression. These brain changes may represent independent and complementary pathways to dementia and depression. Strategies to slow progression of vascular pathology and neurodegeneration could indirectly prevent both dementia and depression in older adults.